2014
DOI: 10.1371/journal.pone.0105198
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Rice, Noodle, and Bread Intake and Sleep Quality in Japanese Men and Women

Abstract: BackgroundPrevious studies have shown that a diet with a high-glycemic index is associated with good sleep quality. Therefore, we investigated the association of sleep quality with the intake of 3 common starchy foods with different glycemic indexes–rice, bread, and noodles–as well as the dietary glycemic index in a Japanese population.MethodsThe participants were 1,848 men and women between 20 and 60 years of age. Rice, bread, and noodle consumption was evaluated using a self-administered diet history questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 43 publications
3
27
0
1
Order By: Relevance
“…Magnesium could enhance the secretion of melatonin by stimulating serotonin N -acetyltransferase activity [25], as well as act as a γ-aminobutyric acid agonist to improve sleep [26]. However, inconsistent results were reported in a cross-sectional study among Japanese adults [8]. Therefore, further studies on the associations and their underlying mechanisms between long-term consumption of starchy staple food and sleep quality are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium could enhance the secretion of melatonin by stimulating serotonin N -acetyltransferase activity [25], as well as act as a γ-aminobutyric acid agonist to improve sleep [26]. However, inconsistent results were reported in a cross-sectional study among Japanese adults [8]. Therefore, further studies on the associations and their underlying mechanisms between long-term consumption of starchy staple food and sleep quality are needed.…”
Section: Discussionmentioning
confidence: 99%
“…A high carbohydrate intake was reported to be associated with poor sleep quality among middle-aged female Japanese workers [7]. Another study reported that the direction of association between carbohydrates and sleep quality were different due to the glycemic index of each food, such as rice, bread, and noodle [8]. Recent results from a Chinese cohort reported that dinner fat intake and soy isoflavone were associated with sleep parameters over five years [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Sehubungan dengan jenis makanan yang dikonsumsi, Yoneyamai dkk mengungkapkan bahwa responden dengan konsumsi beras yang tinggi memiliki kualitas tidur yang baik, dan responden dengan konsumsi mi yang tinggi berkorelasi dengan kualitas tidur yang buruk. 16 Studi yang dilakukan oleh St-Onge dkk menyatakan bahwa beberapa makanan seperti konsumsi susu, ikan, buah-buahan serta sayuran dapat memberikan efek yang mempromosikan tidur. 17 Penelitian yang dilakukan oleh penulis di Fakultas Kedokteran Universitas Udayana diikuti oleh mahasiswa dengan jenis kelamin berbeda serta latar belakang kebudayaan yang beranekaragam.…”
Section: Pendahuluanunclassified
“…Likewise, as noted by Masters () and Roundtree (), the impact of alcohol is well documented: Drinking alcohol before bedtime may help induce sleep but also contributes to waking up in the middle of the night. Studies have also shown that overall diets (e.g., high‐glycemic diets; Yoneyama et al, ) are associated with improved sleep and that eating certain foods can improve sleep. For example, Lin, Tsai, Fang, and Liu () found that kiwifruit eaten 1 hour before bedtime reduced the time to fall asleep and increased total sleep time and efficiency among adults between 20 and 55 years of age, and Garrido et al () found that ingestion of tart cherry juice increased total sleep time and sleep efficiency among small samples of middle‐aged (ages 35–55) and older adults (ages 65–85).…”
Section: Lifestyle and Stressmentioning
confidence: 99%